Using qualitative and community-based engagement approaches to gain access and to develop a culturally appropriate STI prevention intervention for foreign female entertainment workers in Singapore - Raymond Boon Tar Lim; Olive N. Y. Cheung; Dede Kam Tyng Tham; Hanh Hao La; Thein Than Win; Roy Chan; Mee Lian Wong (BMC, 2018)
Abstract Background There is an increasing global movement of foreign female entertainment workers (FEWs), a hard-to-reach population vulnerable to HIV/STIs. This paper described the needs assessment phase before intervention implementation where the socio-organisation, sexual risk behaviours and access to health services of foreign FEWs in Singapore were explored. We also highlighted how qualitative inquiry, census enumeration technique and community-based engagement approaches were used to gain access and to develop a culturally appropriate STI prevention intervention. Methods In-depth interviews, observations, informal conversational interviews, mystery client and critical incident technique were used. We estimated the size of FEW population using the census enumeration technique. The findings were used to inform intervention development and implementation. Results We estimated 376 Vietnamese and 330 Thai FEWs in 2 geographical sites where they operated in Singapore. Their reasons for non-condom use included misconceptions on the transmission and consequences of STI/HIV, low risk perception of contracting HIV/STI from paid/casual partner, lack of skills to negotiate or to persuade partner to use condom, unavailability of condoms in entertainment establishments and fear of the police using condom as circumstantial evidence. They faced difficulties in accessing health services due to fear of identity exposure, stigmatisation, cost and language differences. To develop the intervention, we involved FEWs and peer educators, and ensured that the intervention was non-stigmatising and met their needs. To foster their participation, we used culturally-responsive recruitment strategies, and ensured that the trial was anonymous and acceptable to the FEWs. These strategies were effective as we achieved a participation rate of 90.3%, a follow-up rate of 70.5% for the comparison and 66.8% for the intervention group. The interventions group reported a significant increase in consistent condom use with a reduction in STI incidence compared to no significant change in the comparison group. Conclusions The qualitative inquiry approaches to gain access, to foster participation and to develop a culturally appropriate intervention, along with the census enumeration technique application to estimate the FEW population sizes has led to successful intervention implementation as well as safer sexual behaviour and STI incidence reduction. Trial registration ClinicalTrials.gov, NCT02780986. Registered 23 May 2016 (retrospectively registered).